Pelatihan Kerja Untuk Mengurangi Turnover Karyawan Di PT Mtrix Mitra Telekomunikasi - Lestari, Tria Cavita; Shalahuddin, Shalahuddin (JURNAL MAHASISWA BINA INSANI; Vol 7 No 2 (2023): Jurnal Mahasiswa Bina Insani (Februari 2023), 2023)
The background of this problem is taken from the high turnover rate of technician employees at PT Matrix Mitra Telekomunikasi so that it affects employee performance and also slows down their duties and responsibilities and can hinder the success of an organization or company. The purpose of this study is to handle employee turnover through providing job training to technician employees in the hope of reducing employee turnover and providing knowledge for technician employees so that their work runs smoothly. The research method used is a qualitative method where in the process direct interviews with the HR department and employees of PT Matrix Mitra Telekomunikasi are conducted. The result of this research is the lack of provision in knowledge or expertise from the company for technician employees so that it can slow down the work of technician employees. From the results of interviews according to the operational division, the training program is very effective in reducing the high turnover rate on the part of technicians, especially ip pabx and voip training because in this field of work technicians require special skills. The conclusion of this research is PT Matrix Mitra Telekomunikasi can make training program activities into a policy in the form of company SOPs, so that training programs for technician employees can run according to company policy and run smoothly.